Susceptibility to ceftriaxone and occurrence of penicillinase plasmids in Neisseria gonorrhoeae strains isolated in Poland in 2012-2013 - Mlynarczyk-Bonikowska, Beata; Kujawa, Marlena; Mlynarczyk, Grazyna; Malejczyk, Magdalena; Majewski, Slawomir (Folia microbiologica, 2016)
Recent years have seen rising concerns over increasing antibiotic resistance of the gonorrhea-causing bacterium, Neisseria gonorrhoeae. This is especially true for third-generation cephalosporins, which are currently recommended for the treatment of such infections. Therefore, susceptibility to these antibiotics should be monitored internationally to the greatest extent possible. The susceptibility of N. gonorrhoeae strains to ceftriaxone and penicillin, as well as production of beta-lactamase by the Cefinase test was determined. Moreover, the presence and type of penicillinase plasmids were determined by PCR. All strains were susceptible to ceftriaxone, the minimal inhibitory concentration (MIC) values ranged from 0.002 to 0.125 mg/L; MIC50 was =0.016 mg/L and MIC90 was =0.064 mg/L. As much as 7.7 % of the strains demonstrated ceftriaxone MIC of 0.125 mg/L. For penicillin, the MICs ranged from 0.064 to 32 mg/L; MIC50 was =0.5 mg/L and MIC90 was =4 mg/L. It was shown that only 1.5 % of the strains were sensitive to penicillin according to The European Committee on Antimicrobial Susceptibility Testing (EUCAST). Among the penicillin-resistant strains, six (30.0 %) produced penicillinase. The MICs of penicillin were substantially higher for penicillinase-producing than for penicillin-resistant, penicillinase-negative strains. MICs of ceftriaxone for penicillinase-producing strains were low (0.002-0.016 mg/L). Three of the penicillinase-producing strains possessed plasmids of African type (50 %) and three Toronto/Rio type (50 %). An increase of the proportion of beta-lactamase-positive strains in the last years as well as emergence of strains with elevated MIC of ceftriaxone indicate a need to constantly monitor N. gonorrhoeae strains for their susceptibility to beta-lactam antibiotics, as well as for their ability to produce beta-lactamases.
Keywords: Female; mikrobiální testy citlivosti; Polsko; ženské pohlaví; lidé; Anti-Bacterial Agents; cefalosporiny; Microbial Sensitivity Tests; gonorea; Male; plazmidy; Cephalosporins; Gonorrhea; peniciliny; Penicillins; ceftriaxon; penicilinasa; Penicillinase; Neisseria gonorrhoeae; Ceftriaxone; Plasmids; mužské pohlaví; Poland; antibakteriální látky; Humans